1990
DOI: 10.1002/cber.19901231111
|View full text |Cite
|
Sign up to set email alerts
|

Geminale Substituenteneffekte, 4. Abhängigkeit des inversen anomeren Effektes geminaler Nitril‐Gruppen von der Struktur

Abstract: Geminal Substituent Effects, 4. — The Dependence of the Inverse Anomeric Effect of Geminal Cyano Groups on the Structure The heats of combustion and the heats of sublimation of malodinitrile (1a), ä‐alkyl‐ (1b,c) and å, å‐dialkylmalodinitriles (1 d ‐f) have been determined. From the obtained standard heats of formation group increments for CH2[CN]2], CH[(CN)2 Cl and C[CN)2C2] group are deduced. The comparison of their values with corresponding increments for monocyano alkanes reveals a synergetic destabilisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…These confirm that malononitrile and butane-dinitrile are distinct cases, and higher species follow the formula Equation (15b). This is supported by Beckhaus et al [27], who reported, in a paper on geminal substituent effects, a synergetic destabilization by two geminal cyano substituents of 11.5 kcal/mol or 48 kJ/mol. In their paper, they also evaluated the heat of formation and found 266.5 kJ/mol for malononitrile, in good agreement with the NIST value in Table 5.…”
Section: ∆H F (Mononitriles) = Gc Ch 3 + N Ch 2 * Gc Ch 2 + Gc Cn (15a)supporting
confidence: 52%
See 3 more Smart Citations
“…These confirm that malononitrile and butane-dinitrile are distinct cases, and higher species follow the formula Equation (15b). This is supported by Beckhaus et al [27], who reported, in a paper on geminal substituent effects, a synergetic destabilization by two geminal cyano substituents of 11.5 kcal/mol or 48 kJ/mol. In their paper, they also evaluated the heat of formation and found 266.5 kJ/mol for malononitrile, in good agreement with the NIST value in Table 5.…”
Section: ∆H F (Mononitriles) = Gc Ch 3 + N Ch 2 * Gc Ch 2 + Gc Cn (15a)supporting
confidence: 52%
“…Thus, malononitrile is considered a regular molecule for which the heat of formation is purely additive with first-order contributions, namely, for CH 2 CN and CN only. Based on the energy differences between successive species in the series, and our ab initio and DFT calculations and the work by Beckhaus et al [27], we have to conclude that the MG ICAS23 results are not based on the correct chemistry.…”
Section: ∆H F (Mononitriles) = Gc Ch 3 + N Ch 2 * Gc Ch 2 + Gc Cn (15a)mentioning
confidence: 59%
See 2 more Smart Citations
“…As a result it was shown that electron donating substituents like alkoxy groups (in acetals [2,11] and ortoesters [7]) or amino groups (in aminales [8]) experience synergetic stabilization, generally called "anomeric stabilization," which is mainly caused by 7r-a* conjugation (a through bond effect). On the contrary, combinations of electron-withdrawing substituents (CN, COOR, COR) show a destabilizing synergetic effect [1,5,9,13] mainly caused by repulsive interaction through space. We turn our attention in this publication to the geminaI interaction of .…”
Section: Introductionmentioning
confidence: 99%